HUBUNGAN GAYA KEPEMIMPINAN TRANSFORMASIONAL DENGAN KINERJA PERAWAT DI RUANG RAWAT INAP PADA MASA PANDEMI COVID-19 DI RSU KABUPATEN TANGERANG TAHUN 2021 - Sartiyah, Sartiyah; Ngasu, Kristina Everentia; Septimar, Zahrah Maulidia (Nusantara Hasana Berdikari, 2022)
Leaders have their own leadership styles, one of which is transformational leadership style, where this transformational leadership style can provide motivation and change in the workplace environment. Research objectives to find out the relationship of transformational leadership style with the performance of nurses in the inpatient room during the Covid-19 pandemic in RSU Tangerang Regency. The research uses quantitative research design with a Cross Sectional approach. The sample technique used by this study is a saturated sampling technique or total sampling with a sample number of 108 respondents. Transformational leadership styles category good 61 (56.5%). Special performance of nurses category good 78 (72.2%). General performance of category good 58 nurses (53.7%). 56 (91.8%) have a transformational leadership style good and good to the performance of nurse-specifics. 48 (78.7%) have a transformational leadership style that is good and good for the general performance of nurses. There is a transformational leadership style relationship with nurse-specific performance with A Value of 0.000 and OR 12.72. There is a transformational leadership style relationship with the general performance of nurses with a P Value of 0.000 and an OR of 13.66. There is a transformational leadership style relationship with nurse performance.